2021
DOI: 10.1007/s10479-021-04021-3
|View full text |Cite
|
Sign up to set email alerts
|

Vertical value-added cost information sharing in a supply chain

Abstract: We study a two-echelon supply chain with two homogeneous manufacturers and one common retailer who has full knowledge about his own value-added service cost structure that is unknown to the manufacturers. The retailer may choose to disclose his cost information to the manufacturers. Using a three-stage game-theoretic model, we derive optimal pricing strategies for each participant, and optimal information sharing strategies, and the optimal level of the value-added services for the retailer. Our study also rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Therefore, some enterprises provide value-added services to attract low-carbon consumers. In general, cost data associated with value-added services is often considered private information for retailers [19]. In practice, supply chain members usually possess private information that is unknown to outsiders, so they are inclined to protect their cost information to maximize profits [20].…”
Section: Author(s)mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, some enterprises provide value-added services to attract low-carbon consumers. In general, cost data associated with value-added services is often considered private information for retailers [19]. In practice, supply chain members usually possess private information that is unknown to outsiders, so they are inclined to protect their cost information to maximize profits [20].…”
Section: Author(s)mentioning
confidence: 99%
“…In practice, supply chain members usually possess private information that is unknown to outsiders, so they are inclined to protect their cost information to maximize profits [20]. Asymmetry in value-added service efficiency affects optimal price decisions and service investments [19,21]. Thus, the question arises as to whether retailers will share information about value-added services with manufacturers.…”
Section: Author(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings showed that sharing information is not always beneficial in competitive scenarios. Similarly, Liu et al (2021) considered a two-echelon supply chain with two homogeneous manufacturers and a retailer to study retailer's decisions on sharing cost information about the value-added services. They found that the optimal level for value-added services is mainly determined by the retailer's service cost efficiency and information sharing does not always create a win-win situation in a supply chain.…”
Section: Supply Chain Contracts With Information Asymmetry Issuesmentioning
confidence: 99%
“…According to the findings of Ha and Tong [33], they showed that contracts of generating information sharing is essential as a value driver of information sharing and the ability to share information in order to gain a competitive advantage under competition between supply chains. Furthermore, contracts are also used to promote coordination and encourage information sharing in case of information asymmetry [34]. H6: Contract influences opportunities to share information.…”
Section: Relational Resourcesmentioning
confidence: 99%